Development and characterization of shape memory Cu-Zn-Al thin films - Haberkorn, N. (2010)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina